Graphene Oxide affects Staphylococcus aureus and Pseudomonas aeruginosa dual species biofilm in Lubbock Chronic Wound Biofilm model - Di Giulio, Mara (Sci Rep, 2020)
Chronic wound management becomes a complex procedure because of the persistence of forming biofilm pathogens that do not respond to antimicrobial treatment. The aim of this paper is to detect the Graphene Oxide-GO effect on Staphylococcus aureus and Pseudomonas aeruginosa dual species wound biofilm in Lubbock Chronic Wound Biofilm-LCWB model. LCWB is a recognized model that mimics the spatial microbial colonization into chronic wounds and reproduces the wound and its clot. Staphylococcus aureus PECHA 10 and P. aeruginosa PECHA 4, are the pathogens used in the study. The GO effect on both in forming and mature biofilms, is detected by the evaluation of the CFU/mg reduction, the cell viability and ultrastructural analysis of the treated LCWBs. Graphene Oxide, at 50 mg/l, shows a significant antibiofilm effect in forming and mature LCWBs. In particular, during the biofilm formation, GO reduces the S. aureus and P. aeruginosa growth of 55.05% ± 4.73 and 44.18% ± 3.91 compared to the control. In mature biofilm, GO affects S. aureus and P. aeruginosa by reducing their growth of 70.24% ± 4.47 and 63.68% ± 17.56, respectively. Images taken by SEM show that GO display a disaggregated microbial effect also disrupting the fibrin network of the wound-like biofilm framework. In conclusion, GO used against microorganisms grown in LCWB, displays a significant inhibitory action resulting in a promising tool for potential application in wound management.